Burden of diabetes and hypertension among people attending health camps in an urban area of Kancheepuram district - Hariharan, S.; Umadevi, R.; Stephen, T.; Pradeep, S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes and hypertension are among the most common non-communicable diseases affecting our population. They are the important risk factors for cardiovascular morbidity and mortality. The aims and objectives of the study were to determine the burden of diabetes and hypertension among people attending health camps in an urban area of Kancheepuram district. Formulation of suitable preventive measures based on the inferences from the study. Methods: A cross- sectional record based study was done on 825 people attending medical camps conducted by Sree Balaji Medical College & Hospital, in Anakaputhur area of Kancheepuram district. The data regarding Random Blood Sugar (RBS) level, blood pressure level, age, and gender were collected from the camp register (January and February, 2017). A random blood sugar (RBS) value of >200 mg/dl in a patient with classic symptoms of hyperglycaemia or hyperglycaemic crisis was defined as having diabetes. Blood pressure level equal to or greater than 140/90mm Hg was defined as having hypertension. Descriptive analysis and Chi square test was done to see the statistical association between various parameters. Results: Of the total study population of 825 people, 215 were males and 610 were females. The overall burden of diabetes and hypertension among the study population was 10.7% and 6.4% respectively. Co-existence of both diabetes and hypertension was seen in 5.7% of people. Conclusions: To reduce the disease burden due to diabetes and hypertension, primary prevention measures such as health education regarding adoption of healthy lifestyle should be instituted. Interventions such as screening and early initiation of treatment should also be made for controlling the diseases and preventing its complications.